Essays in honor of M. Hashem Pesaran. - Chudik, Alexander; Hsiao, Cheng, 1943-; Timmermann, Allan; Pesaran, M. Hashem, 1946- (Advances in Econometrics Ser., 2022)
The collection of chapters in Volume 43 Part A of Advances in Econometricsserves as a tribute to one of the most innovative, influential, and productive econometricians of his generation, Professor M. Hashem Pesaran.